FACTORS AFFECTING FOREIGN DEBT IN OIC COUNTRIES - Sjafruddin; Inayah Swasti Ratih; Bahrina Almas; Robby Reza Zulfikri (CV. Radja Publika, 2024)
This study looks at how current balance deficit, GDP, and government spending affect foreign debt in eight countries in the Organization of Islamic Cooperation: Lebanon, Jordan, Egypt, Pakistan, Morocco, Bangladesh, Kazakhstan, and Algeria. This research uses a quantitative method with data from 2010 to 2020. It uses panel data to explain information between units and cross sections. The results showed that the current balance deficit had no significant effect on foreign debt, but GDP and government expenditure had a significant effect.